Penyuluhan dan Pelatihan Pembuatan Pupuk Organik PSB (Photosyntetic Bacteria) di Desa Sendangdalem Kecamatan Padureso Kabupaten Kebumen - Barokah, Umi; Jannah, Mastsani Durrotul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Community service activities in the form of counseling and training in making organic fertilizers based on Photosynthetic Bacteria (PSB) have been carried out in Sendangdalem Village, Padureso District, Kebumen Regency on June 3, 2025. This activity aims to improve the knowledge and skills of farmers and village youth in the application of organic agriculture and environmentally friendly PSB fertilizer manufacturing technology. The implementation of the activity began with coordination and preparation, followed by counseling on the concept and benefits of organic farming, as well as direct PSB fertilizer making training, where participants were actively involved in each stage of the process. Evaluation is carried out through pre test and post test to measure the effectiveness of activities. The results of the evaluation showed an increase in the average score of participants from 66.82 in the pretest to 70.59 in the post test, which indicated an increase in the understanding and skills of the participants. However, some participants have not experienced a significant increase, so further assistance is needed. Overall, this activity has a positive impact in supporting sustainable agriculture efforts and increasing the capacity of village communities in managing agricultural resources independently and environmentally friendly